PENGARUH PEMBERIAN BIOMASSA Tithonia diversifolia DAN BAKTERI ASAM LAKTAT TERHADAP PERTUMBUHAN JAGUNG, KETERSEDIAAN FOSFOR DAN ALUMUNIUM PADA TANAH ULTISOL - Rahayu Rahayu; Sumani Sumani; Supriyadi Supriyadi; Nafiatul Umami (Caraka Tani: Journal of Sustainable Agriculture, 2012)
One of the potential soil to increase food production in Indonesia is Ultisols but having problems in abiotic stresses especially high exchangeable Aluminum (Aldd) and low pH. This study aimed to determine the effect of Tithonia diversifolia biomass and lactic acid bacteria to increase soil phosphor, reduce aluminum toxicity and promote maize plant growth in Ultisol. Experimental design was completely ramdomized design with 3 factors such as the addition of lactic acid bacteria in the carrier, compost biomass of Tithonia diversifolia and phosphor fertilizer. Application of Lactic Acid Bacteria and Tithonia and P fertilizers simultaneously increasing maize plant growth and reduce Aldd especially on a month after application.